2021
DOI: 10.1108/jfp-05-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and the physical health impacts of forensic workplace trauma

Abstract: Purpose Health-care professionals working in inpatient forensic mental health settings are exposed to a range of traumatic and distressing incidents with impacts discussed variously as “burnout”, “compassion fatigue”, “secondary trauma stress” and “vicarious traumatisation”. This study aims to explore the short- and long-term psychological and physical health effects of trauma exposure in the workplace for frontline staff in a forensic setting. Design/methodology/approach Semi-structured interviews were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…Much like others working within the CJS, police prosecutors in the current study found it easier to seek help from trusted individuals who understood the complexities of their role, because it was easily accessible, informal and validating (Birze, Regehr, & Regehr, 2022a;Duran & Woodhams, 2022;R. Kim, 2021;Mistry et al, 2022;Perez et al, 2010;Ravera, 2022;Te Miha, 2023). The constraints of confidentiality, and not wanting to burden those around you have also been observed in other helping professionals (R. Kim, 2021;Te Miha, 2023;Weir et al, 2021;Wijeratne et al, 2021).…”
Section: Phase Four: Strategies For Managing Wellbeing In the Rolesupporting
confidence: 54%
“…Much like others working within the CJS, police prosecutors in the current study found it easier to seek help from trusted individuals who understood the complexities of their role, because it was easily accessible, informal and validating (Birze, Regehr, & Regehr, 2022a;Duran & Woodhams, 2022;R. Kim, 2021;Mistry et al, 2022;Perez et al, 2010;Ravera, 2022;Te Miha, 2023). The constraints of confidentiality, and not wanting to burden those around you have also been observed in other helping professionals (R. Kim, 2021;Te Miha, 2023;Weir et al, 2021;Wijeratne et al, 2021).…”
Section: Phase Four: Strategies For Managing Wellbeing In the Rolesupporting
confidence: 54%
“…Nurses caring for patients who self‐harm are therefore at increased risk of generalized stress response, negatively impacting their well‐being from an accumulative effect of exposure to traumatic events and increased use of risk‐adverse, controlling practices (Morris et al, 2022). Maladaptive coping strategies, such as increased alcohol consumption and changes to diet/eating patterns, in response to accumulative exposure to traumatic events and use of restrictive practices may also affect nurses' physical health (Mistry et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, nurses working on acute units had comparable mental health to nurses working on nonacute units, despite having significantly greater exposure to patient aggression. Individual differences regarding impact of exposure to patient aggression among forensic mental health staff working on one unit has also been reported (Mistry et al, 2022), indicating factors other than unit type also influence impact. Influencing factors may be protective and include individuals' resilience and well-being and access to support, supervision and incident debriefing (Mistry et al, 2022).…”
Section: Impact Of Exposure To Patient Aggressionmentioning
confidence: 95%
See 2 more Smart Citations